1989
DOI: 10.1021/jm00121a044
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C analogs with a substituted hydrazine at position 7. Synthesis, spectral properties, and biological activity

Abstract: A select number of mitomycin C derivatives with a substituted hydrazine group at position 7 were synthesized and tested for antineoplastic activity by using an in vivo test with murine P388 leukemia. Several of the adducts displayed activity comparable to that of mitomycin C. The X-ray-determined crystal structure of one of the derivatives (3f) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mitomycins are multifunctional molecules (). Although strategies to modify the C(7) ( ) and N (1a) ( ) loci exist, we chose to attach the antisense oligodeoxynucleotide to the C(10) site in the mitomycin (). Preliminary molecular modeling experiments indicated that mitomycins tethered at this site would permit subsequent DNA bonding at C(1) with minimal distortion of the DNA duplex .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitomycins are multifunctional molecules (). Although strategies to modify the C(7) ( ) and N (1a) ( ) loci exist, we chose to attach the antisense oligodeoxynucleotide to the C(10) site in the mitomycin (). Preliminary molecular modeling experiments indicated that mitomycins tethered at this site would permit subsequent DNA bonding at C(1) with minimal distortion of the DNA duplex .…”
Section: Resultsmentioning
confidence: 99%
“…The values for purines, pyrimidines, and porfiromycin at 260 nm were considered to be 14 000, 7000, and 12 000, respectively; the values for porfiromycin and DNA at 360 nm were considered to be 23 000 and 0, respectively (41,42) (40). Although strategies to modify the C(7) (44)(45)(46)(47) and N(1a) (48)(49)(50) loci exist, we chose to attach the antisense oligodeoxynucleotide to the C(10) site in the mitomycin (51). Preliminary molecular modeling experiments indicated that mitomycins tethered at this site would permit subsequent DNA bonding at C(1) with minimal distortion of the DNA duplex.…”
Section: Conjugation Of the N-[10-decarbamoyl-10-o-thiocarbonyl-[n(1a...mentioning
confidence: 99%
“…The organic layer was washed with brine, dried over Na2S04, and concentrated on a rotary evaporator. The residue obtained was purified by preparative TLC (silica gel, 9:1 CHCl3-MeOH as a developing solvent) followed by trituration with CHCl3-7i-hexane and drying under vacuum to afford 12a (10 mg, 31%) as a red powder: NMR (270 MHz, pyridinedb) 2.17 (dd, J = 2.2, 4.6 Hz, 1 , 2-H), 2.25 (s, 3 H, la-CH3), 2.55 (d, J = 4.6 Hz, 1 H, 1-H), 3.20 (s, 3 H, 9a-OCH3), 3.48 (dd, J = 2.2, 12.6 Hz, 1 , 3 -), 3.60 (s, 3 H, 7-OCH3), 3.99 (dd, J = 4. 4, 11.3 Hz, 1 , 9-H), 4.22 (d, J = 12.6 Hz, 1 H, 3/3-H), 4.80 (br t, J = 10.9 Hz, 1 H, 10-Ha), 5.35 6.6-Dibromo-7-demethoxy-6-demethyl-7,7-(ethylenedioxy)-6,7-dihydromitomycin B (21).…”
Section: Methodsmentioning
confidence: 99%